2019
DOI: 10.1364/ol.44.001536
|View full text |Cite
|
Sign up to set email alerts
|

Physical secure optical communication based on private chaotic spectral phase encryption/decryption

Abstract: We propose and demonstrate a novel physical secure high-speed optical communication scheme based on synchronous chaotic spectral phase encryption (CSPE) and decryption (CSPD). The CSPE is performed by a module composed of two dispersion components and one phase modulator (PM) between them, and the CSPD is carried out by a twin module with reverse dispersions and inverse PM driving signals. The PM driving signals of the CSPE and CSPD modules are privately-synchronized chaotic signals that are independently gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(49 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…Owing to the considerable importance of optical chaos demonstrated in communication systems such as physical random bit generation [1-3], chaotic radars [4], secure-communications [5][6][7], optical time-domain reflectometer (OTDR) [8], optical neuron [9], Brillouin optical correlation-domain analysis (BOCDA) [10], optical chaos generation process has recently attracted very great research attention. Basically, the optical feedback into semiconductor laser used to produce chaotic signal was mainly limited in application performances due to the monopolization of chaos RF spectrum by the laser relaxation oscillation frequency [11] and time-delay signature (TDS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the considerable importance of optical chaos demonstrated in communication systems such as physical random bit generation [1-3], chaotic radars [4], secure-communications [5][6][7], optical time-domain reflectometer (OTDR) [8], optical neuron [9], Brillouin optical correlation-domain analysis (BOCDA) [10], optical chaos generation process has recently attracted very great research attention. Basically, the optical feedback into semiconductor laser used to produce chaotic signal was mainly limited in application performances due to the monopolization of chaos RF spectrum by the laser relaxation oscillation frequency [11] and time-delay signature (TDS) [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, these schemes are limited by the processing speed of electronics [6], [7], and the MAC layer of an optical network is more susceptible to malicious attacks [5]. Therefore, researchers have turned their attention to the security of the physical layer of optical networks thanks to the fast development of unique and ultra-fast properties of optical signal processing [3], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, he proposed a physical WDM transmission by using chaotic spectral phase encryption where the phase modulator was driven by chaos from a chaos optical injection and a mirror feedback [22]. It was shown that the security of transmission arises partly from the complication of the driving signal of phase modulator, since any small difference from the authorized scheme prevents unauthorized attacks from decrypting the transmitted messages [22].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, he proposed a physical WDM transmission by using chaotic spectral phase encryption where the phase modulator was driven by chaos from a chaos optical injection and a mirror feedback [22]. It was shown that the security of transmission arises partly from the complication of the driving signal of phase modulator, since any small difference from the authorized scheme prevents unauthorized attacks from decrypting the transmitted messages [22]. Also, the weak correlation between driving chaos synchronization signals and transmission carriers can improve the security performance in chaos communication, since such weaker correlation inhibits eavesdroppers illegal attacks from replicating the scheme of communication [21].…”
Section: Introductionmentioning
confidence: 99%